An Approach for Sensory Effects Dispersion Simulation with Computational Fluid Dynamics - Rodrigues, Renato; Silva Jr., José Ricardo da; Brandão, Diego; Santos, Joel dos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
The inclusion of sensory effects in multimedia applications has the potential to increase the Quality of Experience (QoE) and improve users immersion. However, authoring such applications presents challenges arising from the need to control the rendering of sensory effects in the physical environment along with the presentation of their counterpart in the multimedia application and the constantly changing sensory effects state according to user interaction. Computational Fluid Dynamics (CFD) techniques can be used to simulate the sensory effects in a virtual environment and use the generated data to automatically control actuators. In this work, we propose an architecture to simulate wind sensory effects in an interactive real-time application and validate it using a CFD method. Data from simulation is then used to infer propagation delay and the wind temperature at the user position.